Construction de l’expérience et formation hybride : transformations de l’activité de professeurs des écoles instrumentée par la plateforme M@gistère - Frédéric Pogent (Recherches en Éducation)
In view of the widespread use of digital technology in all human activities, it seems essential to examine the changes in activity, particularly in the working environments that concern human development. Since the Ministry of National Education (MEN) has been promoting hybrid training (M@gistère) since 2013 - alternating classroom and distance learning for school teachers (PE) – it seemed appropriate to investigate the actual use and conditions under which this training offer produces learning and possibly changes classroom practices. The performed survey shows that if PE do not connect much to the platform, some imposed courses are consulted by those who then declare that they are changing their classroom practice. The objective was to document the activity of the PE on the remote platform. It was a question of identifying what, in the training environment, makes a device, to understand what instruments the construction of the experience and the way it occurs in training.